The Effectiveness of Monetary Policy since the Onset of the Financial Crisis - Bouis, Romain (OECD Economics Department Working Papers, 2013)
In the wake of the Great Recession, a massive monetary policy stimulus was provided in the main OECD economies. It helped to stabilise financial markets and avoid deflation. Nonetheless, GDP growth has been sluggish and in some countries lower than expected given the measures taken, and estimated economic slack remains large. In this context, this paper assesses the effectiveness of monetary policy in recent years. It finds that notwithstanding an almost full transmission of policy interest rate cuts and unconventional policy measures to higher asset prices and lower cost of credit in and outside the banking sector in most countries, with the exception of vulnerable euro area economies, monetary policy stimulus did not show up in stronger growth due to a combination of three factors. First, lower policy interest rates may not have provided as much stimulus as expected given the evidence of a decrease in natural interest rates, resulting from the estimated decline in potential GDP growth in the wake of the crisis. Second, balance sheet adjustments of non-financial companies and households, large uncertainty as well as simultaneous and considerable fiscal consolidation in many OECD countries constituted important headwinds. Third, the bank lending channel of monetary policy transmission appears to have been impaired, mainly due to considerable balance sheet adjustments and prevailing uncertainty, which together limited banks' capacity and willingness to supply credit. The paper also stresses that the monetary accommodation risks having unintended negative consequences which are likely to increase with its duration